The Potency of Microalgae as a Marine Source: A Bibliometric Analysis - Witasari, Hardi Astuti; Kintoko, Kintoko; Ahda, Mustofa; Rangkuti, Ahmad Faizal; Suhendra, Suhendra; Mahfudh, Nurkhasanah (Journal of Food and Pharmaceutical Sciences, 2025)
Microalgae were a marine source that was highly sustainable and offered numerous benefits in industrial applications. Many species were safe and effective as active ingredients in the food, cosmetics, and pharmacy industries and became raw materials for renewable energy, such as biofuel. The exploration of bioactive compounds was enticing for the research. The study of microalgae potency is a fascinating subject that deserves further exploration. The bibliometrics analysis can provide a good overview of microalgae research and its applications in industry. This overview was derived from the Scopus database, which contained all articles published between 1993 and 2023 with the keywords "microalgae" and "their application. Based on this discovery, many papers reported the potential of microalgae for antioxidants, nutrition, vaccine adjuvants, bioethanol, biofuel, and other applications for 2021-2022. This review criticizes the cultivation in a controlled environment up to the toxicity of microalgae. According to this review, many researchers focused and collaborated on exploring microalgae in the top three international journals, such as Algal Research, Marine Drugs, and Journal of Applied Phycology. Several countries, including Italy, Spain, and China, were the most focused on declaring the application of microalgae. The keywords described the core discussion and could be read generally and comprehensively. This bibliometric analysis was expected to contribute to developing microalgae for many applications.